El invierno - Thayer, Tanya (Minneapolis : Ediciones Lerner, 2006)
Simple text and color photographs identify things associated with winter.
Includes index.
In Spanish.
Keywords: Winter -- Juvenile literature; Spanish language materials; Winter; Seasons; Spanish language materials; Materiales en espanol